A klímaváltozás káros hatása a szőlőre (Irodalmi kitekintés) - Knolmajer, Bence (GEORGIKON FOR AGRICULTURE, 2022)
Continuous climate change affects the whole biosphere. Anthropogenic activity is accelerating this naturally occurring process. Climate is an important factor in agriculture, and thus in viticulture, as it has a fundamental impact on the habitat of plants and animals. The new conditions pose a new challenge to vine growers, with the current warming trend creating largely unfavourable conditions. On the one hand, direct damage (sun damage, drought, frosts, hailstorms, etc.) and, on the other hand, indirect damage (emergence of new pathogens: Aspergillus sp., Xylella fastidiosa) are putting an extra burden on farmers. Extreme weather events have become more frequent, and uneven rainfall and drought are a particular problem for viticulture. Extreme weather forces producers to make extra heavy investments: irrigation, ice nets, frost protection. In addition to the high cost of planting, the sector is also characterised by labour shortages. With current grape purchase prices, high input prices and the cost of irrigation, which is slowly becoming essential for crop security, planting does not pay for itself. In order to mitigate the effects of climate change, researchers are creating opportunities for adaptation through continuous technological improvements. The long-term physiological impact of some of these techniques is not yet known. These technologies can be used to influence the duration of vine development, ripening time and quality parameters.
Keywords: climate change; global warming; viticulture; abiotic stress